2017
DOI: 10.1002/jip.1483
|View full text |Cite
|
Sign up to set email alerts
|

Male‐on‐male sexual assault: Victim, offender and offence characteristics

Abstract: Unlike male-on-female sexual assaults, little is known about the nature of male-on-male sexual assault, especially in terms of victim, offender and offence characteristics. The present paper systematically reviews the limited research into male-on-male sexual offences in order to ascertain the current state of knowledge with regards to these issues. An extensive search resulted in the identification of 15 empirical studies, with a total of 5,112 cases of male-onmale sexual assaults, for inclusion in the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…What little demographic information was given in prior military reports regarding male-on-male offenders were consistent with civilian population studies, which state that most male-on-male offenders are found to be White with a heterosexual orientation, are an average age of 25.8 years, and act alone when committing their crimes (Hazelwood and Burgess 2009;Ioannou et al 2017). Sexually violent crimes most often occur within the victim or offender's home, have some level of physical or verbal violence including threats, weapons use, or both, and include various sexual acts with the most common being anal penetration or the victim being forced to perform oral sex on the offender (Ioannou et al 2017;Matthews et al 2018).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…What little demographic information was given in prior military reports regarding male-on-male offenders were consistent with civilian population studies, which state that most male-on-male offenders are found to be White with a heterosexual orientation, are an average age of 25.8 years, and act alone when committing their crimes (Hazelwood and Burgess 2009;Ioannou et al 2017). Sexually violent crimes most often occur within the victim or offender's home, have some level of physical or verbal violence including threats, weapons use, or both, and include various sexual acts with the most common being anal penetration or the victim being forced to perform oral sex on the offender (Ioannou et al 2017;Matthews et al 2018).…”
Section: Introductionsupporting
confidence: 63%
“…Male-on-male sexual assaults are one of the most underreported and understudied areas of criminal investigations (Ioannou et al 2017;Lowe and Rogers 2017). Although there is a budding growth in the research of adult male victimization, very few studies have attempted to address the offender dynamics of these crimes outside of prison and institutional environments (Greathouse et al 2015;Ioannou et al 2017;Lowe and Rogers 2017). Noteworthy myths regarding offenders and victims persist, leaving a dearth of information and limiting our understanding of these acts (Ioannou et al 2017;Javid 2018;Lowe and Rogers 2017;Turchik et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Same sex SH has an emerging body of literature (e.g. Forsman 2017;Ioannou et al 2017), and SH toward those presenting or appearing to present as outside of heterosexuality, marginally explored too (e.g. Paulk et al 2017;Cantor et al 2019;Johnson and Otto 2019).…”
mentioning
confidence: 99%